β-adrenergic Regulation of Late Na(+) Current During Cardiac Action Potential Is Mediated by Both PKA and CaMKII - Bence, Hegyi (J Mol Cell Cardiol, 2018)
Late Na+ current (I(NaL)) significantly contributes to shaping cardiac action potentials (AP) and increased I(NaL) is associated with cardiac arrhythmias. β-adrenergic receptor (βAR) stimulation and its downstream signaling via protein kinase A (PKA) and Ca(2)+/calmodulin-dependent protein kinase II (CaMKII) pathways are known to regulate I(NaL). However, it remains unclear how each of these pathways regulates I(NaL) during the AP under physiological conditions. Here we performed AP-clamp experiments in rabbit ventricular myocytes to delineate the impact of each signaling pathway on I(NaL) at different AP phases to understand the arrhythmogenic potential. During the physiological AP (2 Hz, 37°C) we found that I(NaL) had a basal level current independent of PKA, but partially dependent on CaMKII. PAR activation (10 nM isoproterenol, ISO) further enhanced I(NaL) via both PKA and CaMKII pathways. However, PKA predominantly increased I(NaL) early during the AP plateau, whereas CaMKII mainly increased I(NaL) later in the plateau and during rapid repolarization. We also tested the role of key signaling pathways through exchange protein activated by cAMP (Epac), nitric oxide synthase (NOS) and reactive oxygen species (ROS). Direct Epac stimulation enhanced I(NaL) similar to the PAR-induced CaMKII effect, while NOS inhibition prevented the βAR-induced CaMKII-dependent I(NaL) enhancement. ROS generated by NADPH oxidase 2 (NOX2) also contributed to the ISO-induced I(NaL) activation early in the AP. Taken together, our data reveal differential modulations of I(NaL) by PKA and CaMKII signaling pathways at different AP phases. This nuanced and comprehensive view on the changes in I(NaL) during AP deepens our understanding of the important role of I(NaL) in reshaping the cardiac AP and arrhythmogenic potential under elevated sympathetic stimulation, which is relevant for designing therapeutic treatment of arrhythmias under pathological conditions.